Identifying the challenges to defence reform in Central and Eastern Europe: observations from the field. Issue 2 (3rd April 2018) - Grant, Glen; Milenski, Vladimir
ABSTRACT: The authors have over 50 years' experience of working on defence in Central and Eastern Europe. They have been intimately involved in trying to reform over 10 national defence organisations including Ukraine. During this work, they often faced intractable resistance and scepticism or conversely, apparent unbounded support, but following this, a complete lack of any actual implementation work by officials. This paper addresses some of the findings and observations identified by the authors that appear to cause these responses and the consequent failure of reform. A new research approach has been taken by using the business and culture tools from Schein, Hofstede and Kotter to try and unravel the underlying causality of that failure. The second part of the paper produces a new process for change based upon the research conclusions to help other advisers and consultants working on reform in the post communist defence arena.